The Evaluation Of Policies Hedging Transactions with Derivative Instruments - Rahmawati, Teti; Herma Wiharno (Jurnal Riset Keuangan dan Akuntansi, 2025)
The study aims to analyze and obtain empirical evidence to test the effect of internal and external factors on the decision to use derivative instruments in hedging transactions and the disclosure of hedging transactions in the company's annual report. This research is important to obtain data on the determining factors that can encourage companies to carry out hedging transactions and their disclosure in the financial statements. This research was conducted using Logistic Regression analysis. Data were collected from IDX LQ45 from February to June 2023 with purposive sampling so that 34 companies or 170 samples were obtained from 2018-2022. Profitability, leverage, and exchange rate have a significant positive effect on hedging decisions. Thus, the higher the profitability and leverage obtained by the company and the exchange rate also increases, the higher the possibility that the company will make hedging decisions. Meanwhile, liquidity, firm value, and growth opportunity have a significant negative effect on hedging decisions, which indicates that the possibility of hedging transactions will increase if the three variables decrease.